A concession and regulation evaluation of the oil sector in Brazil afterlaw 9.478/97 - Deimling, Márcio Joel; Triches, Divanildo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This paper aims to evaluate the evolution of Brazilian oil market after the national petroleum sector openness. This has taken place with Petroleum Law number 9.478/97 approved by Brazilian government. The methodology was based descriptive statistics analysis of the oil sector regulation data. The new Law has altered the mechanism of income transference from oil production to the government sector. The government sector had increased its proportion of total income by contract of concession and the same time it generated Oil National Agency as well. The results pointed out which this fate brought positive effects to the Brazilian economy in term of investments, industrial diversification and new companies into the oil sector. In last two decades, the oil production has triple fold, from 700.0 thousand to more than 2.0 million of processed barrel by day and the consume jumped from an average 1.6 million of barrel per day among 1990 and 1996 to 2.3 million of barrel per day during 2004 to 2011. The investments were about US 1,6 billion in the beginning the 90’s and they had increase substantially to US 22,5 billion in 2009.